The primary learner's toolkit implementing a creative curriculum through cross-cultural projects, developing social and emotional intelligence, creating independent, confident and lifelong learners - Beere, Jackie (Crown House Pub., 2010)
Suitable for Primary Teachers, this title contains what you need to create truly independent learners, confident and resilient in their ability to learn and learn well. It also includes lessons plans and teachers notes and a CD-ROM in the back of the book that has all the student forms and worksheets necessary for the lessons.